The Effect of Media Composition on the Growth of Fig (Ficus carica L.) Grafts - Didik Pudji Restanto; Moh Nuri Antono; Setiyono Setiyono; Wildan Muhlison; Mohammad Candra Prayoga; Fauziatuz Zahro (Journal of Applied Agricultural Science and Technology, 2025)
The fig plant is cultivated for its fruit due to its high economic value. Vegetative propagation can serve as an alternative for mass propagation of fig plants, such as grafting. Vegetative propagation of figs is conducted in several ways, including grafting and cuttings. The problems encountered in grafting are mainly caused by unsuitable media conditions. This research aims to determine the best composition of grafting media for fig plants. The study was conducted in Dwiwangsa Tin Garden Park, Sidomulyo Village, Krian District, Sidoarjo Regency, East Java. Rainfall at the research site was classified as dry season, with 0 mm in October 2023, 7 mm in November 2023, 150 mm in December 2023, 211 mm in January 2024, and 485 mm in February 2024. The research employed a randomized block design (RBD) consisting of nine media combination treatments. The treatments included soil medium, husk medium, husk charcoal medium, cocopeat medium, sawdust sewing powder medium, a combination of soil and husk medium (1:1), a combination of soil and charcoal husk medium (1:1), a combination of  soil and cocopeat medium (1:1), and a combination of soil and sawdust medium (1:1). Each grafting medium showed a different growth response in terms of root number. Based on the results, the husk charcoal medium produced the highest values, with 89.8 roots, root length of 7.24 cm, root diameter of 1.38 cm, root fresh weight of 5.22 g, root volume of 7.7 ml, and root dry weight of 0.37 g.